O Xkmari wai wai: produção de raladores pelas anciãs na Aldeia Mapuera - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
This work deals with the archaeological importance of the xkmari (cassava graters) made by the Wai Wai women, from the production of these items. From this, show the importance and appreciation of this work by the indigenous people who until today practice the production of graters in the village. The focus of the analysis is the xkmari produced by the indigenous people in the Mapuera village. In order to show how the production process is, the materials used, the meanings of xkmari and the Wai Wai who still practice production. Research shows that the production of an xkmari involves less perishable materials, however, it also involves a series of other materials, mostly perishable, such as wood, resin and pigments. Ethnographies made with the Wai Wai people show that the xkmari were of great value in the exchange networks of the northern Amazon and present information about the production process and meanings of the xkmarí produced by the Wai Wai women. We intend, therefore, to contribute to the appreciation of the work of indigenous women in the production of xkmari.
Keywords: Xkmari; Wai Wai; Etnografia; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS